Current and future immunotherapeutic approaches in Hodgkin lymphoma. Issue 9 (1st September 2016) - Bröckelmann, Paul J.; Borchmann, Peter; Engert, Andreas
Abstract: Hodgkin lymphoma (HL) has become a highly curable malignancy even in advanced stages when treated adequately. However, relapsed or refractory disease and treatment-related toxicity constitute a significant clinical challenge. Innovative approaches are thus needed to improve treatment of these mainly young patients. In HL lesions, very few malignant Hodgkin and Reed-Sternberg (HRS) cells are embedded in an immunosuppressive microenvironment of reactive cells. Novel approaches such as bispecific antibodies, antibody-drug conjugates, immune-checkpoint inhibitors or adoptive cellular therapies are currently being investigated with promising results in relapsed or refractory patients. Encouraging response rates and a favorable toxicity profile have recently been reported in early phase clinical trials with antibodies blocking the programed-death receptor 1 (PD1). This review will summarize the current clinical knowledge on mechanism, safety and efficacy of the different agents and discuss potential future strategies, which are partly already investigated within clinical trials.